Bathymetric trends in the body size, and diet of Astropecten americanus in the northwest Atlantic Ocean. (31st May 2022) - Adebola, Tunde; Hart, Deborah; Chigbu, Paulinus
Abstract: Sea stars are major predators of marine invertebrates, in particular, mollusks. Data on the diet composition and the size structure of sea stars in the N.W. Atlantic Ocean are limited. Samples of sand star ( Astropecten americanus ) collected from three regions in the N.W. Atlantic Ocean were used to determine spatial and seasonal differences in diet and size structure. Samples were collected from ten stations during the 2009 spring and fall NMFS bottom trawl surveys. Four hundred and eighty-eight (488) prey items belonging to various taxa were identified from stomach contents of 524 sea stars of which 302 contained food. In terms of percentage contribution by number of prey items belonging to each taxon (Cn%), gastropods (40%), bivalves (22%) and crustaceans (21%) were the most important. Gastropods were more important in the diet of Southern New England (SNE) and Mid-Atlantic Bight (MAB) sea stars accounting for ∼50% of the diet in each area, and were consumed by 35–42% of the sea stars, whereas crustaceans were more important in Georges Bank (GB) where they contributed ∼83% of the diet, and were consumed by about 77% of the sea stars. There were more gastropods and foraminiferans in the stomachs of sea stars collected in fall, while crustaceans and bivalves were more common in spring samples. These differences may be due to spatial and seasonal differences in the abundance and composition of macrobenthic invertebrates. The size of sea stars decreased with depth, perhaps due to a reduction in prey abundance and higher sea star densities with depth. Additionally, length-weight relationships suggest that sea stars in GB were heavier at a given size (length) than those from SNE and MAB. This might have resulted from the latitudinal variation in the density and species composition of macrobenthic invertebrates that serve as prey for sea stars, such that densities were low on the continental shelf off Delaware-Virginia-North Carolina and relatively high in the region off southern Massachusetts and Rhode Island. Highlights: Diet and size structure of sand star ( Astropecten americanus ) in the N.W. Atlantic Ocean varied spatially and seasonally. Gastropods were more important in the diet of Southern New England (SNE) and Mid-Atlantic Bight (MAB) sea stars; crustaceans were more important in their diet in Georges Bank (GB) sea stars. Mean size of sea stars decreased with depth, perhaps due to a reduction in prey abundance and higher sea star densities with depth. Sea stars in GB were heavier at a given length than those from SNE and MAB.